Organizing the Storage of Grape Products - Yangiboevich, Sharipov Sultan; Bakhodir, Rozimov Shamsiddin (American Journal of Biology and Natural Sciences, 2025)
This article discusses one of the most important fruits for your Republic today, not only in the domestic market, but also in the export sector. The main task in preserving grapes is to preserve their physical and chemical composition, that is, their appearance, texture, taste, and nutritional value. The article presents a detailed study of the biological and physiological processes involved in preserving grapes and information on the factors affecting product quality indicators.